2015
DOI: 10.1039/c5ra09897a
|View full text |Cite
|
Sign up to set email alerts
|

Selective removal of transition metal ions from aqueous solution by metal–organic frameworks

Abstract: 5Water stable Zr-based metal-organic frameworks (MOFs) with different functional groups were used for selective removal of Cu 2+ over Ni 2+ from aqueous solution. Due to the unique chelation effect of two carboxyl groups on the adjacent organic ligand as well as the Jahn-Teller effect, UiO-66(Zr)-2COOH exhibits the highest selectivity (up to about 27) for Cu 2+ /Ni 2+ in aqueous solution among the reported adsorbents as far as we know. In addition, the removal process is fast with less than 60 min for 10 equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In lower pH environments, protons in solution compete with Cu(II) and Cr(VI) for the bonding sites on the adsorbent. 32,33 Cr 2 O 7 2À , HCrO 4 À or CrO 4 2À co-existed at pH 6.0, and HCrO 4 À existed as the dominant form. 34,35 HCrO 4 À possesses greater affinity toward the proton on the surface; this specic pH environment favored the adsorption process.…”
Section: Effect Of Ph On Cu(ii) and Cr(vi) Adsorptionmentioning
confidence: 92%
See 1 more Smart Citation
“…In lower pH environments, protons in solution compete with Cu(II) and Cr(VI) for the bonding sites on the adsorbent. 32,33 Cr 2 O 7 2À , HCrO 4 À or CrO 4 2À co-existed at pH 6.0, and HCrO 4 À existed as the dominant form. 34,35 HCrO 4 À possesses greater affinity toward the proton on the surface; this specic pH environment favored the adsorption process.…”
Section: Effect Of Ph On Cu(ii) and Cr(vi) Adsorptionmentioning
confidence: 92%
“…The removal efficiency of Cr(VI) at pH 7 and 8 is inferior to that at pH 6. In lower pH environments, protons in solution compete with Cu(II) and Cr(VI) for the bonding sites on the adsorbent 32,33. Cr 2 O 7 2À , HCrO 4 À or CrO 4 2À co-existed at pH 6.0, and HCrO 4…”
mentioning
confidence: 99%
“…Table displays the adsorptive removal of Cu­(II) onto the Zr-MOFs enhanced by cross-flow disturbance of ceramic membrane as compared to other different adsorbents and methods in terms of adsorption capacities under certain conditions. From these data, it can be seen that the adsorption capacity of the method proposed by this study is significantly higher than the other cases that were previously reported. ,, In the other words, Zr-MOFs enhanced by cross-flow disturbance of ceramic membrane have great potential ability for significantly high removal of Cu­(II) from heavy metal wastewater.…”
Section: Resultsmentioning
confidence: 50%
“…After the accidental discovery of enhanced adsorption of Pb­(II) combined with ceramic membrane in one of our previous works, no one uses the relative method to enhance the adsorption removal of heavy metal ions. Moreover, the modified Zr-MOF of UiO-66-2COOH only showed a very low capacity of 11.04 mg L –1 for Cu­(II) removal . Because of the different adsorption affinities between Cu­(II) and Pb­(II), the feasibility of the Zr-MOFs for the enhanced removal of Cu­(II) is worthy of study.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), a type of porous material connected by inorganic clusters and organic ligands, have been widely used in liquid-phase adsorption/separation for metal ions. For adsorbents, good stability in aqueous solution and rich adsorption sites are both necessary. In this respect, Zr-based MOFs were found to be commonly stable in water for the high coordination number of Zr atoms.…”
Section: Introductionmentioning
confidence: 99%